A study on adhesive characteristics of double cantilever beam specimens with inhomogeneous materials due to tensile and out-of-plane shear fractures. (15th March 2020) - Kim, J.W.; Cho, J.U.; Cho, C.D.
Abstract: In this study, the adhesive characteristics of double cantilever beam specimens with the inhomogeneous adhesion materials due to tensile and out-of-plane shear fractures have been investigated. The experiments were conducted by applying a forced displacement rate of 3 mm/min at the upper position and fixing the lower position, while each experimental condition was maintained to be identical. In the tensile fracture of mode Ⅰ, the maximum reaction force was observed to be highest in the order of CFRP-Al, Al–Al_Foam, and CFRP-Al_Foam. The maximum energy release rate was highest in the order of Al–Al_Foam, CFRP-Al, and CFRP-Al_Foam. When the overall crack resistance curves were examined, all of the highest energy release rates could be seen to be produced at an early stage of cracking. In mode Ⅲ, the maximum reaction force was highest in the order of CFRP-Al, Al–Al_Foam, and CFRP-Al_Foam. The maximum energy release rate was observed to be highest in the order of CFRP-Al, CFRP-Al_Foam, and Al–Al_Foam. Considering that the higher reaction forces and energy release rates were produced in the specimen containing, it could be inferred that the use of a material with high rigidity increased the maximum strength of the adhesive.